KELIMPAHAN DAN KEANEKARAGAMAN PARASITOID PADA PERTANAMAN MENTIMUN (Cucumis sativus) - Sumeinika Fitria Lizmah; Damayanti Buchori; Akhmad Rizali (Jurnal Agrotek Lestari, 2018)
Abundance and diversity of parasitoids is strongly associated with the presence of pests and vegetation around cucumber plantings. This study aims to determine the abundance and diversity of parasitoid species in cucumber plantings. The research was conducted at four cucumber planting locations in Bogor, West Java. Insect sampling is done using yellow pantraps and malaise traps. The results show the highest species abundance obtained at the Cibatok of 632 individuals and the lowest in Cibanteng 197 individuals. The highest Shannon-Wiener index value at Cangkurawuk is 4.2927 and the evenness of species is 0.92. The high abundance of individuals is not always accompanied by the higher value of diversity and evenness too.Keywords: abundance, cucumber, diversity, parasitoid